PROTOTYPE JEMURAN OTOMATIS MENGGUNAKAN SENSOR RAINDROP DAN SENSOR LIGHT DEPENDENT RESISTOR (LDR) BERBASIS ARDUINO NANO - Tri Susanti; Dedi Setiadi (Universitas PGRI Semarang, 2022)
Research has been to produce a system that can help facilitate the process of drying clothes, so that it can handle the process of drying clothes. The system development method used in this study is the RAD (Rapid Application Development) method which has stages, namely requirements planning, workshop design and implementation, data collection techniques, namely observation, interviews, literature study, and documentation. The software used is the Arduino IDE application. The tool that will be designed will work automatically, Raindrop sensor to detect raindrops, so that when it rains, clothes will automatically fall under the roof. LDR sensor to detect the weather in dark or light. Stepper motor to move clothes as detected. The components used are Arduino Nano, Raindrop Sensor, LDR Sensor, Breadboard, Driver Module, Jumper Cable, and Stepper Motor. Based on the results of the Prototype Automatic Clothesline Using a Raindrop Sensor and a Light Dependent Resistor (LDR) Sensor Based on Arduino Nano which has been successfully processed on the Raindrop Sensor, namely when it rains it detects and does not detect rain, the LDR Sensor, which is when the weather is bright, it detects and in dark weather it doesn't. detect. With an automatic clothesline, so that it can help Nugraha Laundry employees and the community in handling clothes drying.